Effects of dexamethasone coadministered with oseltamivir on the pharmacokinetics of oseltamivir in healthy volunteers - Jang, Kyungho (Drug Des Devel Ther, 2017)
PURPOSE: Oseltamivir is widely used in the treatment and prophylaxis of influenza A and B viral infections. It is ingested as an oral prodrug that is rapidly metabolized by carboxylesterase 1 (CES1) to its active form, oseltamivir carboxylate. Dexamethasone is also used in the treatment of acute respiratory distress syndrome, a severe complication of influenza; however, its influence on the pharmacokinetics (PK) of oseltamivir is controversial. The aim of this study was to investigate the effects of coadministering oseltamivir and dexamethasone on the PK of oseltamivir in healthy volunteers. METHODS: An open-label, two-period, one-sequence, multiple-dose study was conducted in 19 healthy male volunteers. Oseltamivir (75 mg) was orally administered on Day 1 and Day 8, and dexamethasone (1.5 mg) was administered once daily from Day 3 to Day 8. Serial blood and urine samples were collected for PK analysis of oseltamivir and oseltamivir carboxylate on Day 1 and Day 8. Oseltamivir and oseltamivir carboxylate concentrations in plasma and urine were determined using liquid chromatography–tandem mass spectrometry. RESULTS: Area under the plasma concentration–time curve (AUC) of oseltamivir and oseltamivir carboxylate decreased after dexamethasone treatment for 6 days. The geometric mean ratio (90% confidence interval) of the metabolic ratio (oseltamivir carboxylate AUC(0–48h)/oseltamivir AUC(0–48h)) was 0.92 (0.87–0.97). The amount of unchanged oseltamivir excreted in urine increased by 14% after dexamethasone treatments. CONCLUSION: Coadministration of dexamethasone with oseltamivir slightly decreased systemic exposure to oseltamivir and oseltamivir carboxylate in healthy volunteers. This result suggests that CES1 is inhibited by dexamethasone in humans. However, coadministration of oseltamivir and dexamethasone did not appear to have a clinically relevant effect on the PK of oseltamivir; based on these results, dexamethasone can be coadministered with oseltamivir.